HUBUNGAN KADAR NEURON SPECIFIC ENOLASE SERUM TERHADAP LUARAN KLINIS NEUROLOGIS PASIEN STROKE ISKEMIK AKUT - Christina Roseville Lasma Aritonang,* Retnaningsih,* Amin Husni* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION STROKE IS A NEUROLOGICAL DISEASE THAT CAUSE DISABILITY ISCHEMIC STROKE OCCURS IN 8587 OF ALL CASES THE BIOCHEMICAL MARKERS OF ACUTE NEURON INJURY CAN HELP IN DIAGNOSIS AND MANAGEMENT OF CEREBROVASCULAR INJURY NEURON SPECIFIC ENOLASE NSE IS DIMERIC ISOENZYMES OF GLYCOLYTIC ENOLASE ENZYMES AND FOUND MAINLY IN NEURONS AS ONE OF THE MARKERS IN ACUTE NEURONAL INJURY AND CAN BE ESTIMATED TO ASSESS SHORTTERM NEUROLOGICAL OUTCOME